Construindo uma vida por meio da escrita: Roque Gonzáles de Santa Cruz e seu processo de beatificação (séculos XVII-XX) - Nunes, Jefferson Aldemir (Universidade do Vale do Rio dos Sinos, 2021)
This dissertation has the focus on the Jesuit Roque Gonzáles de Santa Cruz, a Paraguayan missionary killed by Guarani indians in 1628, in Caaró, Rio Grande do Sul. His death was the beginning of a long process of canonization, which would take 360 years to be complete. This work seeks answers that expose the reason for this long period. The general objective is to analyze the process of institutionalization of the veneration of Roque Gonzáles de Santa Cruz in its various layers, relating it to the historiographical treatment, political environment and interest groups involved in his canonization. This will be done by analyzing the bibliography about him, and the 1932 beatification process, which had not been analyzed by previous authors. The methodology is centered on the discussion and use of operational concepts and debates such as holiness (Woodward, Cunningham, Matos, Gallick Piccone Camere); biography, trajectory and hagiography (Certeau, Loriga, Le Goff, Schmidt, Sobral, Bourdieu, Levi, Borja Gomes, Del Priore, Dosse, Karsburg); global community of martyrs (Cymbalista); the cause and process of beatification/canonization (Soares); and social construction of holiness (Soares). The work’s conclusions point to the complex relationship between the subjects who made an effort to close the beatification process. Furthermore, as the story of Gonzáles needs to be thought of in a broader way, from new perspectives that include the participation of social agents to form a support group that ensured that his canonization was completed.
Keywords: Roque Gonzáles; Jesuítas; Santidade; Trajetória; Jesuits; Holiness; Historical trajectory; ACCNPQ::Ciências Humanas::História